Progressive and Asymmetrical Deadlift Loads Captured by Wearable Motion Tape Sensors - Elijah Wyckoff; David Sten; Regan Wareham; Kenneth J. Loh (Sensors)
Weight training is widely adopted and highly effective for enhancing both muscular strength and endurance. A popular weightlifting exercise is the deadlift, which targets multiple muscle groups including the lower back, glutes, and hamstrings. However, incorrect technique (i.e., poor form) can slow training progress, result in asymmetrical muscle development, and cause serious injuries. The objective of this study was to validate that a self-adhesive, elastic fabric, wearable, skin-strain sensor called Motion Tape (MT) could monitor a person’s posture while performing deadlift exercises. Two pairs of Motion Tape were attached on the front and back sides of the pelvis at each posterior superior iliac spine to record muscle engagement during deadlift exercises. The results of this preliminary study confirmed that the MT identified asymmetry in muscle engagement during deadlifting repetitions. In addition, the sensors could quantify the different levels of effort exerted according to the deadlift weight load.